Hubungan Antara Self-Control Dengan Perilaku Konsumtif Pada E-Commerce Dikalangan Mahasiswa Gen Z - Ika Prawesti Andini; Moh Sarifudin S Auna; Isniarty Gintulangi (PSYCHONESIA: JOURNAL OF PSYCHOLOGY, 2025)
Gen Z is a digital generation that tends to behave in a consumptive manner because it is influenced by a digital lifestyle as evidenced by data on buying and selling via e-commerce which is dominated by Gen Z with a percentage of 77%. This study aims to determine how strong the relationship is between self-control and consumptive behavior in e-commerce among Gen Z students. The research method used is a quantitative method with a correlational design. The respondents in this study numbered 63 people who were selected using a purposive sampling technique. The results of the Spearman Rank data analysis showed that there was no significant relationship between self-control and consumptive behavior (p = 0.981). These results indicate that there are other factors such as gender, emotional motivation, and social norms that influence a person's consumptive behavior. So it is hoped that further researchers can explore other variables that can influence a person's consumptive behavior.